Aspects of the formation of pain syndrome in the area of the masticatory muscles in the disease of the maxillary-mandibular composition - Olimov S.Sh; Bakaev J.N.; Safarovа M.J. (International Journal on Human-Computing Studies, 2021)
The article describes modern aspects of the formation of pain syndrome in the area of the masticatory muscles in the disease of the maxillary-mandibular composition. The author presented an extensive review of the literature of foreign and swollen students, detailed the main factors of the formation of pain syndrome in the disease of the maxillary-mandibular composition. Common hairstyles for pain syndrome describe modern approaches to conducting and planning treatment.